2021
DOI: 10.3389/frobt.2021.673730
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots as Creativity Eliciting Agents

Abstract: Can robots help children be more creative? In this work, we posit social robots as creativity support tools for children in collaborative interactions. Children learn creative expressions and behaviors through social interactions with others during playful and collaborative tasks, and socially emulate their peers’ and teachers’ creativity. Social robots have a unique ability to engage in social and emotional interactions with children that can be leveraged to foster creative expression. We focus on two types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 55 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…Research describes different types of creativity, as well: (1) figural creativity, related to the development of visual artifacts (i.e., drawing, painting, sketching) [19], (2) performance creativity [20], related to the creation of performance arts (i.e., music, dance, theater), (3) constructional creativity [4], which represents building and tinkering (e.g., using LEGO blocks), and (4) verbal creativity, related to the verbal presentation of ideas and thoughts (i.e., writing, storytelling, poetry) [19].…”
Section: A Background On Creativitymentioning
confidence: 99%
See 2 more Smart Citations
“…Research describes different types of creativity, as well: (1) figural creativity, related to the development of visual artifacts (i.e., drawing, painting, sketching) [19], (2) performance creativity [20], related to the creation of performance arts (i.e., music, dance, theater), (3) constructional creativity [4], which represents building and tinkering (e.g., using LEGO blocks), and (4) verbal creativity, related to the verbal presentation of ideas and thoughts (i.e., writing, storytelling, poetry) [19].…”
Section: A Background On Creativitymentioning
confidence: 99%
“…For instance, a recent study [5] showed that participating in an activity to program a robot had a higher positive impact on children's creativity skills than participating in one to design a robot or participating in a music activity. In a different setting, children participated in three one-to-one creativitycollaborative tasks with a JIBO robot to address verbal, figural and constructional creativity [4], [6], [31]. The authors aimed to investigate the effects of the robot's creative behavior on children's creativity skills.…”
Section: Creativity In Child-robot Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already, pedagogical agents have been shown to scaffold valuable learning behaviors like creativity, growth mindset, curiosity, empathy, and grit. The agents modelled these positive behaviors, then guided and encouraged users to display these behaviors during interactive activities [17]- [19]. This led to significant increases in students expressing and acting out these behaviors.…”
Section: Future Workmentioning
confidence: 99%
“…Recently, researchers in HAI have attributed great attention to the study of how to use agents in order to stimulate children's creativity. Previous research suggests that artificial agents exhibiting creativity skills positively impact children's creativity [1,2,3]. Researchers have assessed children's creativity after an interaction with a creative agent by using various types of tasks.…”
Section: Introductionmentioning
confidence: 99%